2011
DOI: 10.1890/10-1170.1
|View full text |Cite
|
Sign up to set email alerts
|

Microbes do not follow the elevational diversity patterns of plants and animals

Abstract: Abstract. The elevational gradient in plant and animal diversity is one of the most widely documented patterns in ecology and, although no consensus explanation exists, many hypotheses have been proposed over the past century to explain these patterns. Historically, research on elevational diversity gradients has focused almost exclusively on plant and animal taxa. As a result, we do not know whether microbes exhibit elevational gradients in diversity that parallel those observed for macroscopic taxa. This rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

30
249
13

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 352 publications
(300 citation statements)
references
References 45 publications
30
249
13
Order By: Relevance
“…However, we do acknowledge that microbial diversity was also related to abundance and we therefore cannot exclude different growth rates, for instance, contributing to the biodiversity patterns. Several studies have predicted how microbial community composition may vary with altitude, but the relationship between microbial diversity and altitude remains debated (Bryant et al, 2008;Fierer et al, 2011). Our findings on functional traits and diversity shed new light on this relationship for stream biofilms.…”
Section: Discussionmentioning
confidence: 67%
“…However, we do acknowledge that microbial diversity was also related to abundance and we therefore cannot exclude different growth rates, for instance, contributing to the biodiversity patterns. Several studies have predicted how microbial community composition may vary with altitude, but the relationship between microbial diversity and altitude remains debated (Bryant et al, 2008;Fierer et al, 2011). Our findings on functional traits and diversity shed new light on this relationship for stream biofilms.…”
Section: Discussionmentioning
confidence: 67%
“…In this survey, Bryant et al found that soil Acidobacteria exhibited a declining pattern of phylogenetic diversity with increasing altitude, whereas Angiosperm showed a typical unimodal pattern. Another comparative study between the diversity patterns of macroorganism and microorganism along an elevational gradient from 200 to 3,450 m in the eastern Peru montane areas observed no clear pattern for the bacterial diversity, whereas plants and animals exhibited a significant pattern of decline [11]. In addition, a significant unimodal pattern of soil bacterial diversity along an elevational gradient was reported on the Mt.…”
Section: Introductionmentioning
confidence: 97%
“…Comparative studies are common in biogeography; however, most of microbial biogeographic studies have focused merely on bacteria [11] or archaea [16]. In fact, both bacteria and archaea have been found to be remarkably abundant and functionally important in terrestrial ecosystems, and could contribute differently to ecosystem functioning and biogeochemical cycling [17].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have investigated the elevation gradients of soil MB at sites below 3000 m (Arunachalam and Pandey, 2003;Djukic et al, 2010;Fierer et al, 2011). These studies conducted on Mt.…”
Section: Introductionmentioning
confidence: 99%